Penerapan LKPD sebagai Upaya Meningkatkan Rasa Ingin Tahu Siswa Kelas VII pada Pembelajaran IPA di SMPN 1 Sanrobone - Syarifah Hijrah Febrianti; Asy Syifa; Resdi, Resdi; Riza Sativani Hayati (Pusat Riset dan Inovasi Nasional, 2026)
In the learning process, educators often face challenges in helping students achieve optimal learning outcomes. One of the contributing factors is the dominance of teacher-centered learning models, which frequently leads to low student engagement and reduced motivation. This condition affects students’ curiosity, particularly in Science learning, which requires active participation and exploration. Therefore, innovative teaching materials are needed to encourage student involvement while simultaneously stimulating their curiosity. One alternative that can be utilized is the Student Worksheet (Lembar Kerja Peserta Didik/LKPD), which can be designed systematically and contextually to support active learning. This study aims to determine the effectiveness of using LKPD in enhancing students’ curiosity in Grade VII Science learning at SMPN 1 Sanrobone. The research employed a Classroom Action Research (CAR) approach carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The findings indicate a significant increase in students’ curiosity after the implementation of LKPD, as shown by improvements in questioning behavior, interest in the material, and the ability to observe and explore scientific phenomena. Based on these results, it can be concluded that the use of LKPD is effective in fostering students’ curiosity and contributes to a more interactive and meaningful Science learning experience.